Our clinical experience with pediatric patients after May 2003 Bingöl earthquake - Özel, Ş. Kerem; Kazez, Ahmet; Çeliker, Hüseyin; Yildirim, A. Mustafa; Parmaksiz, Ergün; Yilmaz, Erhan; Pekdemir, Murat (My University, 2004)
Aim: The aim of the study is to evaluate the pediatric patients who were admitted to our hospital after May 2003 Bingöl earthquake. Method: Totally 16 patients between the ages of 4 months to 16 years were evaluated retrospectively. The patients were investigated according to the time spent under the rubble, type of the injury, mode of treatment, development of acute renal failure (ARF) and crush syndrome (CS), complications, laboratory findings in patients with crush injury (CI) and their prognosis. Results: The mean age of the 16 patients among the total 61 earthquake victims who were transferred to our hospital were 11.4±1.3 years. Mean time spent under the rubble was 10.7±2 hours. CI was seen in 10 patients whereas CS in 2 of these 10 patients, soft tissue injury in 4, head trauma in 4, bone fracture in 2 and peripheral nerve injury during the initial admission in 2. In 7 of 10 CI patients myoglobinuria was observed however ARF developped in only 2. In patients with CS and CI the mean serum urea levels were 26.1±8.3 mg/dl, creatinine 0.94±0.5 mg/dl and potassium 4.85±1.3 mmol/L. These normal results were explained with early agressive fluid resussitation started at the scene. Fasciotomy was done in 5 patients with CI. Hemodialysis was performed in 2 patients with ARF. All of the wounds of fasciotomy healed uneventfully. No death was observed. Peripheral nerve injury developed in 4 patients, bleeding and tissue loss in 2 patients, DIC (disseminated intravascular coagulation) in 2 patients and fat emboli in 1 patient. Conclusion: Agressive fluid resussitation started at the scene may have a decremental effect on the development of ARF in earthquake victims. As it has many complications, fasciotomy should be performed if a meticulous wound care can be done and with definite indication. The treatment protocols for these patients should be well recopnized in countries with the risk of earthquakes like Turkey.
Mayis 2003 Bingöl depremi sonrasi çocuk hastalardaki klinik deneyimlerimiz
Keywords: Children; Crush injury; Earthquakes; Multiple trauma